USING HAND PUPPETS AS MEDIA TO IMPROVE STUDENTS’ SPEAKING SKILL THROUGH NARRATIVE TEXT: A CASE OF EIGHTH STUDENTS OF SMP N 16 SEMARANG IN ACADEMIC YEAR OF 2016/2017 - Chintia Ardhiani; Arso Setiyaji; Jafar Sodiq; Dias Andris Susanto (ETERNAL (English Teaching Journal), 2021)
The objectives of this study are (1) to find out the students of speaking skills who are taught using hand puppet. (2) To find out the students of speaking skills who are taught without using hand puppet. (3) To find out any significant difference speaking skills of students who are taught with and without using hand puppet. In order to the objectives of the study, relevant theories were refer to and discussed significance among them were theories of speaking, storytelling, learning media, and hand puppets. Following the presentation of the theoretical frameworks, the research methods were selected. The study used quantitative description with experimental approach.  Based on the data analysis, the research found that the result of the significant difference speaking skill of students who are taught with and without using hand puppets through narrative text. According to statistical calculations, sig. (2-tailed) and with df 33 in significance level 0, 05 t-table = 22.392 with p-value = 0,000 and a = 0, 05. Which is p < a; (0,000 < 0, 05). It proved that Hº was rejected and H¹ accepted.